Industrial wood from natural forests or plantation - some aspects. - Awang, Kamis; Mohamed, Shukri (1986)
The paper examines the relative importance of natural forests and plantations as sources of industrial wood for Malaysia, from the point of view of supply, harvesting, utilization, quality and economics. Natural forests are expected to contribute less to the total industrial wood requirement in the future. In contrast, plantations are becoming a more important source of wood. Harvesting of the natural forests will be drastically reduced, more in line with the sustained yield concept. Experience in the harvesting of plantation forests is limited, though it is expected to be relatively easier. Future utilization of the natural forests is envisaged to encompass a wider range of species in view of the fast depletion of the resource. The market acceptance of the plantation species is still unclear, although their properties indicate promosing utilization potential. Logs of the natural forests are more varied in terms of species and properties but generally of bigger size and good form. Plantation logs are expected to be more uniform but relatively smaller in size. Economically, plantation forestry is a more attractive venture than natural forestry. In the final analysis, plantations are seen as a supplement/complement to the natural forests as the source of industrial wood.